Erisipelas - Wizar Putri Mellaratna; Rizqa Shafrina (Pusat Riset dan Inovasi Nasional, 2023)
Erysipelas is an infection of the nonnecrotic superficial skin accompanied by lymphangitis. This infection will cause a clinical picture in the form of well-defined erythematous plaques. Most cases of erysipelas are caused by bacteria, most often the normal skin flora such as Streptococcus bacteria but erysipelas can also be caused by S. aureus and group C or G Streptococcus. Erysipelas can occur at any age. Erysipelas is closely related to the patient’s physical condition and cellular immune status which underlies or facilitates the occurrence of infections, including chronic systemic diseases suffered by these patients, such as diabetes mellitus, immunocompromised states. The lower extremities are the most common predilection for erysipelas. Most erysipelas patients come for treatment with the main complaint of swelling, redness, and pain experienced by the patient accompanied by other complaints such as burning and itching which are predisposing factors to the occurrence of this infection. The diagnosis of erysipelas is based on anamnesis, physical examination and laboratory tests. The management of erysipelas is the administration of antibiotics and wound care.